Кількісний і якісний склад каннабіноїдних сполук та їх співвідношення у сортів конопель Cannabis sativa L. - Богданова, А.С.; Горшкова, Л.М. (Фактори експериментальної еволюції організмів, 2016)
Aim. With the aim of creating highly productive with the considerable content of cannabinoid the necessity of applying
species with the high level of cannabidiol in the selective work emerges. The influence of different soil and climate zones
on the biosynthesis of these compounds should be researched. Мethods. The quantitative and qualitative analysis of
the cannabinoid compounds was held with the help of the gas and liquid chromatograph Hewlett Packard 5830 A. The
content of cannabinoids was defined with the integrator Hewlett Packard 3380 A. Results. The results of the quantitative
and qualitative analysis proved that the cannabis species Hlukhivs’ka 10 and YUSО-1 synthesized larger amount of
cannabidiol compared to tetrahydrocannabidiol content. Species YUS-6, South Cherkas’ki and Dniprovs’ki 4, except
the north eastern region, had mostly identical content of cannabidiol and tetrahydrocannabidiol. Conclusions. Quantity
and quality content of cannabidiol and tetrahydrocannabidiol was genetically conditioned. The external conditions of
different soil and climate zones facilitated the realization of the specie’s potential. The level of accumulating the separate
compounds in the cannabis species is defined by the complex of the zone conditions which favoured the specie’s genetic
potential.
Keywords: cannabinoids, cannabidiol, tetrahydrocannabidiol, cannabis.